The impact of G7 trade policies on economic development in Africa - Moritz Wolf (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2024)
Economic development in Africa is among the most important global challenges today. Meanwhile, the G7 is under pressure due to system competition and the question of legitimacy and effectiveness. The recent PGII initiative uses investment to improve economic development in Africa. But what about other tools, like trade? While the literature suggests positive effects of trade on economic development, the trade efforts by the G7 have been underwhelming. Moreover, the trade share between Africa and the G7 has decreased over the last two decades. The question if both sides have incentives to reinforce trade links remains and leads to another question, namely if trading with the G7 countries offers specific benefits to African countries. This paper answers this question by using a system-GMM estimator and G7-specific trade data between 1997 and 2020. Using the relative G7 trade share as the explanatory variable and GDP and the HDI as indicators for economic development, the results suggest that both economic growth and human development have been positively affected by G7 trade shares. Moreover, this paper identifies potential channels and concludes that reinforcing the trade relations between the G7 countries and Africa is beneficial for both sides.
Keywords: I31; O19; O24; O55; 330; Africa; Economic Development; Trade; International Organizations